2000
DOI: 10.1038/sj.onc.1203322
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GPC3, an X-linked recessive overgrowth gene, is silenced in malignant mesothelioma

Abstract: Gene expression changes in rat asbestos-induced malignant mesothelioma (MM) cells were investigated by di erential mRNA display. A mRNA transcript identi®ed by this approach was abundant in normal rat mesothelial cells but not expressed in rat MM cell lines. Northern blot analysis con®rmed that this transcript is uniformly silenced in rat MM cell lines and primary tumors. Nucleotide sequence analysis revealed that this transcript is encoded by the rat glypican 3 gene (GPC3), whose human homolog is mutated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
94
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 21 publications
5
94
0
1
Order By: Relevance
“…6 Heparan sulfate proteoglycans are well known to interact with growth factors through heparan sulfate chains and thereby to serve as coreceptors for heparin-binding growth factors. [7][8][9] While studies on ovarian cancer cell lines, mesotheliomas, and breast tumors have demonstrated the downregulation of GPC3, [10][11][12] other investigations on hepatocellular carcinoma have shown a marked elevation of GPC3 mRNA over the level observed in corresponding normal tissues. [13][14][15][16] In the present study, we report the generation of GPC3-C02 and A1836A, a pair of anti-human GPC3 mouse monoclonal antibodies that can detect GPC3 in paraffinembedded tissues by an immunohistochemical technique.…”
mentioning
confidence: 99%
“…6 Heparan sulfate proteoglycans are well known to interact with growth factors through heparan sulfate chains and thereby to serve as coreceptors for heparin-binding growth factors. [7][8][9] While studies on ovarian cancer cell lines, mesotheliomas, and breast tumors have demonstrated the downregulation of GPC3, [10][11][12] other investigations on hepatocellular carcinoma have shown a marked elevation of GPC3 mRNA over the level observed in corresponding normal tissues. [13][14][15][16] In the present study, we report the generation of GPC3-C02 and A1836A, a pair of anti-human GPC3 mouse monoclonal antibodies that can detect GPC3 in paraffinembedded tissues by an immunohistochemical technique.…”
mentioning
confidence: 99%
“…The role of this protein is not yet exactly known. Many studies suggest that GPC3 is a negative cellular growth regulator (Pilia et al, 1996;Weksberg et al, 1996;Cano-Gauci et al, 1999;Lin et al, 1999;Murthy et al, 2000;Xiang et al, 2001), one of the most compelling evidence being that a germline mutation of the gene causes the Simpson -Golabi -Behmel overgrowth syndrome (Pilia et al, 1996) and that Gpc3 knockout mice partly recapitulate the syndrome (Cano-Gauci et al, 1999). On the other hand, GPC3 has been shown to be overexpressed in hepatocellular carcinomas (Hsu et al, 1997;Toretsky et al, 2001;Zhu et al, 2001;Midorikawa et al, 2003) and to be associated with advanced stages as well as with the invasive potential of this cancer (Hsu et al, 1997).…”
mentioning
confidence: 99%
“…As the gene is located on the X chromosome and DNA methylation is implicated in chromosome X inactivation (Monk, 1986), this observation raises the possibility that a loss of methylation could be implicated in the overexpression of GPC3 in some cancer forms. Hypermethylation of the GPC3 promoter associated with gene silencing has been observed in certain adult cancers Lin et al, 1999;Murthy et al, 2000;Xiang et al, 2001). Owing to the potential involvement of GPC3 expression in the aetiology of embryonal tumours, we tested the methylation status of the GPC3 promoter in DNA samples derived from both normal and embryonal tumour cells.…”
mentioning
confidence: 99%
“…11 It has been suggested GPC3 plays a negative role in cell proliferation and an apoptosis-inducing role in specific tissues. 12 The gene is frequently methylated in various tumors and cell lines, [13][14][15] suggesting a tumor-suppressive role in tumorigenesis. However, it is also overexpressed in HCC; 16 recently, both Sung et al 17 and Capurro et al 5 reported GPC3 overexpression in HCC both at messenger and protein level.…”
mentioning
confidence: 99%